2018
DOI: 10.1017/s0007114518003227
|View full text |Cite
|
Sign up to set email alerts
|

Trends of serum phospholipid fatty acids over time in rural Uganda: evidence of nutritional transition?

Abstract: Non-communicable diseases are projected to become the most common causes of death in Africa by 2030. The impact on health of epidemiological and nutritional transitions in sub-Saharan Africa remains unclear. To assess the trends of dietary fatty acids over time in Uganda, we examined fatty acids in serum collected from individuals in rural south-west Uganda, at three time points over two decades. Independent cross-sectional samples of 915 adults and children were selected from the general population cohort in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In an Asian Indian population, it was shown that heating and frying with edible oils (including refined soybean oil, groundnut oil, olive oil, and rapeseed oil) resulted in a significant increase in the amount of both trans and saturated fatty acids from these oils 35 . In addition, a cross-sectional study in Uganda revealed high proportions of saturated, cis-monounsaturated, and trans fatty acids, likely due to the high consumption of palm oil and hydrogenated fats 36 . In the U.S. and many other countries, there are two main types of trans fatty acids: industrial and natural (ruminant) trans fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In an Asian Indian population, it was shown that heating and frying with edible oils (including refined soybean oil, groundnut oil, olive oil, and rapeseed oil) resulted in a significant increase in the amount of both trans and saturated fatty acids from these oils 35 . In addition, a cross-sectional study in Uganda revealed high proportions of saturated, cis-monounsaturated, and trans fatty acids, likely due to the high consumption of palm oil and hydrogenated fats 36 . In the U.S. and many other countries, there are two main types of trans fatty acids: industrial and natural (ruminant) trans fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…This shift in the dietary pattern is commonly called nutrition transition [ 49 , 50 ]. This transition is prevalent in developing countries [ 51 ]. Major demographic and socioeconomic changes of a country paralleled with changes in dietary patterns.…”
Section: Discussionmentioning
confidence: 99%